Hábitos de estudio en los universitarios: consideraciones - Uribe Ruiz, Nérida (2023)
Study habits are fundamental to the academic success of university students. Establishing effective study routines, managing time properly, maintaining concentration and motivation are key elements for optimal academic performance. Good study habits improve understanding, retention, and application of acquired knowledge, and allow efficient time management to avoid procrastination. In addition, they encourage concentration on tasks and self-regulation of study behavior.